Definition of latent antropometric actors of the handball players from the super league of Kosovo - Afrim Koca; Ajvaz Berisha; Erzë Koci (Kazimierz Wielki University, 2018)
The aim of this study is to describe the morphological structure of the handball players and to define the anthropometric factors from morphological structure of players who compete in "Super League" (Superliga) in the Kosovo Handball Championship. Subject of this study were 128 male, active handball players from senior teams who compete in regular competition of the " Super League" in Handball Federation. Players were from eight different teams, sixteen players from each club: H.C. "Trepça", H.C. "Kastrioti", H.C. "Besa Famglia", H.C. "Prishtina",H.C. " Kosova, H.C. " Liridoni", H.C. "Drenica" and H.C. "Vjosa". Anthropometric measurements were conducted in nine anthropometric variables for which the author of this study believes is sufficient for the purpose of this scientific paper. The specific variables were: Body Weight, Body Height, Length of Arms, Length of Hand, Breadth of Hand, Biacromial Breadth, Chest Girth, Waist Girth, and Arm Girth. Measurements are realized by protocol (ISAK) International Scientific Advanced Kinanthropometric . The data was analyzed by statistical package ,they are processed in the SPPS program , version 23.0 for windows. The first purpose of the research was the evaluation of the morphological structure of the all senior teams at the same time, but as well to define the anthropometric factors which affect the players who compete in the same rank of "Super League" (Superliga) in the Kosovo Handball Championship. Through this study we will try to examine the morphological structure of Kosovo handball players from many different teams throughout the cities of Kosovo